THE INFLUENCE OF SELF-BRANDING, BRAND IMAGE ON IMPULSIVE BUYING OF FASHION PRODUCTS IN E-COMMERCE IN TEENAGERS (International Conference on Social and Islamic Studies, 2022)
The latest technological advances make it easier for individuals to do shopping activities, not only done directly but can be done indirectly through E-commerce. As the number of people shopping online from the internet increases, it triggers a variety of unusual online shopping behavior issues. Unnatural online shopping behavior is spending money to buy something that does not match actual needs called Impulsive Buying. Shopping can be used as motivation to improve Self Branding and Brand Image which causes many individuals to make purchases uncontrollably. This study aims to determine the Influence of Brand Image and Self Branding on Impulse Buying of fashion products in E-commerce. The sample data used in this study was obtained through purposive sampling techniques, namely E-commerce users with the characteristic of buying products through E-commerce using their own money, having a minimum purchase frequency of 2x in the last 6 months. This research uses quantitative methods with multiple linear regression analysis techniques. The results of this study show that brand image and self-branding lifestyle have a positive and significant effect on Impulse Buying.